2020
DOI: 10.1088/1361-6579/abc4c7
|View full text |Cite
|
Sign up to set email alerts
|

A review of fetal cardiac monitoring, with a focus on low- and middle-income countries

Abstract: There is limited evidence regarding the utility of fetal monitoring during pregnancy, particularly during labor and delivery. Developed countries rely on consensus ‘best practices’ of obstetrics and gynecology professional societies to guide their protocols and policies. Protocols are often driven by the desire to be as safe as possible and avoid litigation, regardless of the cost of downstream treatment. In high-resource settings, there may be a justification for this approach. In low-resource settings, in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 181 publications
0
5
0
Order By: Relevance
“…Given the higher perinatal mortality rate, the need for remote fetal monitoring in developing countries may be more urgent. Furthermore, a recent review focused on LMICs concluded that mobile technology can overcome economic and geographic barriers by transmitting clinical information collected using low-cost devices, thereby increasing the perinatal care coverage of LMICs [5]. It can be argued that remote fetal monitoring supported by mobile technology appears to have greater potential in LMICs, where antenatal care services need to be improved.…”
Section: Comparison With Prior Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the higher perinatal mortality rate, the need for remote fetal monitoring in developing countries may be more urgent. Furthermore, a recent review focused on LMICs concluded that mobile technology can overcome economic and geographic barriers by transmitting clinical information collected using low-cost devices, thereby increasing the perinatal care coverage of LMICs [5]. It can be argued that remote fetal monitoring supported by mobile technology appears to have greater potential in LMICs, where antenatal care services need to be improved.…”
Section: Comparison With Prior Studiesmentioning
confidence: 99%
“…Fetal monitoring is the primary means of monitoring to assess fetal safety and contributes to reducing the risk of stillbirth by detecting fetal hypoxia as early as possible [2,3]. Previous studies have repeatedly demonstrated the clinical value of fetal monitoring in reducing adverse perinatal outcomes (eg, neonatal cerebral palsy, hypoxic-ischemic encephalopathy, or stillbirth) [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Limited access to complex medical devices for fetal cardiac monitoring in LMICs is well known. However, recent assessments of telemonitoring combined with portable ultrasound have been demonstrated to be more efficacious than the standard of care and yield cost-effective gestational outcomes [1,15].…”
Section: Portable Ultrasound and Hand-held Electrocardiogram Imagingmentioning
confidence: 99%
“…[21][22][23][24][25] Globally, It is estimated that 98% of perinatal deaths occur in low-and middleincome countries. [26] While technologies for the assessment of fetal wellbeing (e.g. fetal electrocardiography, ultrasound imaging and fetal magnetocardiography) are often prohibitively expensive, fetal heart rate monitoring is one of the most affordable solutions.…”
Section: Introductionmentioning
confidence: 99%
“…fetal electrocardiography, ultrasound imaging and fetal magnetocardiography) are often prohibitively expensive, fetal heart rate monitoring is one of the most affordable solutions. [26, 27] Recent efforts have also resulted in the development of significantly cheaper mobile-based technologies. [28] The technical training required for practitioners to use these devices is low.…”
Section: Introductionmentioning
confidence: 99%